Asymptotic analysis of phase averaging of a transport process - Pogorui, A. О. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We investigate asymptotic expansions of solutions of singularly perturbed transport equations in Markov and semi-Markov media.